Hubungan Harga dan Volume Penjualan Buah Lokal dalam Strategi Penentuan Harga Bauran Produk (Kasus pada Ritel UD Moena Farm Sejahtera I) - WAYAN WIDYANTARA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
The Relationship of Price and Sale Volume of Local Fruits in Pricing Strategies of Mix Products (Case in Ritel UD Moena Farm Sejahtera I)Retail stores which are also called retailer have been growing rapidly these days, especially in urban areas. Many retailers specifically sell agricultural commodities such as fruits and vegetables. The objectives of the study were to: (1) determine the correlation between the selling price the commodity of fruits offered between the lines, (2) the effect of the selling price of commodity of fruits on the volume of sales on each line, and (3) determine the sales prospects of each commodity and the maximum revenues from sales in each line of fruits at UD Moena Farm Sejahtera I.The analysis showed that, there was a fairly strong correlation between the price of guava and the selling price of salak Bali. The correlation of selling prices on other commodities (bananas, Lumajang oranges, and Kintamani oranges) was very weak. The selling price which affected the volume of sales occurred in fruit commodity of salak Bali, bananas, oranges Lumajang oranges, and Kintamani oranges. The selling price of guava had no effect on the selling volume. There were two commodities of fruits that had a good prospect, namely: Lumajang oranges, and Kintamani oranges, but these commodities are substitution goods. Salak Bali and banana negatively affected on the sales.